Multiplex polymerase chain reaction detection of selected bacterial species from symptomatic and asymptomatic non‐vital teeth with primary endodontic infections. Issue 2 (11th January 2018) - Pattanshetty, Smita; Kotrashetti, Vijayalakshmi S.; Bhat, Kishore; Nayak, Ramakant S.; Somannavar, Pradeep; Pujar, Madhu
Abstract: Aim: The aim of the present study was to investigate the presence of selective anaerobic microorganisms in primary root canal infections of symptomatic and asymptomatic non‐vital teeth with periapical pathosis using multiplex polymerase chain reaction. Methods: A total of 100 root canal samples (50 from symptomatic and 50 from asymptomatic teeth) were obtained from patients with primary endodontic infections. DNA extracted from the samples was amplified by using specific primers for the 16S rRNA gene of each bacterium, and semiquantification was done to analyze the prevalence of microorganisms and their correlation to clinical features. Results: Treponema denticola ( T. denticola ) was present in 21 (42%) and 29 (58%) samples in the symptomatic and asymptomatic groups, respectively. Tannerella forsythia, Porphyromonas gingivalis ( P. gingivalis ), and Fusobacterium nucleatum ( F. nucleatum ) were significantly high ( P  <   .05) in the symptomatic group, whereas Prevotella intermedia was significantly high ( P  <   .05) in the asymptomatic group. The mean counts of T. denticola and F. nucleatum were significantly high ( P  <   .05) in the symptomatic group. For symptoms, P. gingivalis, T. denticola, and F. nucleatum were significantly associated with clinical features. Conclusion: Significant differences exist in the bacterial composition between asymptomatic and symptomatic primary endodontic infections. As well as presence of pathogens, other factors, such as the phenotypic trait of bacteria and interactions among bacterial members, might play a determining role in the pathogenicity of primary endodontic infections.